Preparation of curcumin self-micelle solid dispersion with enhanced bioavailability and cytotoxic activity by mechanochemistry. (1st January 2018) - Zhang, Qihong; Polyakov, Nikolay E.; Chistyachenko, Yulia S.; Khvostov, Mikhail V.; Frolova, Tatjana S.; Tolstikova, Tatjana G.; Dushkin, Alexandr V.; Su, Weike
Abstract: An amorphous solid dispersion (SD) of curcumin (Cur) with disodium glycyrrhizin (Na2 GA) was prepared by mechanical ball milling. Curcumin loaded micelles were self-formed by Na2 GA when SD dissolved in water. The physical properties of Cur SD in solid state were characterized by differential scanning calorimetry, X-ray diffraction studies, and scanning electron microscope. The characteristics of the sample solutions were analyzed by reverse phase HPLC, UV–visible spectroscopy, 1 H NMR spectroscopy, gel permeation LC, and transmission electron microscopy. In vitro cytotoxic tests demonstrated that Cur SD induced higher cytotoxicity against glioblastoma U-87 MG cells than free Cur. Besides, an improvement of membrane permeability of Cur SD was confirmed by parallel artificial membrane permeability assay. Further pharmacokinetic study of this SD formulation in rat showed a significant ∼19-fold increase of bioavailability as comparing to free Cur. Thus, Cur SD provide a more potent and efficacious formulation for Cur oral delivery.